Single-session Preoperative Embolization and Surgical Resection of Vascular Anomalies: A Case Series - Aravind Rajagopalan, MSc; Nikhil Shah, BS; Narainsai K. Reddy, MS; Sofia Aronson, MD; Akira Yamada, MD, PhD; Shankar Rajeswaran, MD (Plastic and Reconstructive Surgery, Global Open)
Summary:. Vascular anomalies encompass 2 broad classifications including vascular tumors and vascular malformations. The management of vascular anomalies is best approached by a multidisciplinary team. Surgical treatment can offer definitive treatment, but carries several risks such as intraoperative hemorrhage, recurrence, and collateral vascular formations from incomplete resections. Here, we present a case report of 3 patients with different vascular anomalies who were all treated by a multidisciplinary team including interventional radiology and plastic surgery. All underwent preoperative embolization before surgical excision, accomplished under a single anesthetic. Here, we discuss the surgical planning and overall approach to patients presenting with localized vascular anomalies and support the use of preoperative embolization with surgical excision under a single anesthetic as a treatment approach.